Catalytic degradation of chlorinated lignin in pulp bleaching wastewater over immobilized laccase - Zhou, Xue-Fei (Penerbit Universiti Kebangsaan Malaysia, 2022)
The aim of this study was to use molecular sieves (NaY, MCM-48, SSZ-13) and graphene oxide (GO) as supports to immobilize laccase to increase its activity and stability. A series of characterization of immobilized laccases against kinetic parameter and stability were carried out, and it was showed that the GO-immobilized laccase (Lac/GO) was better than molecular sieve-immobilized laccases (Lac/NaY, Lac/MCM, Lac/SSZ) in terms of activity and stability test using ABTS (2,2’-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid)) as substrate. The impacts of enzymatic catalysis on degradation of chlorinated lignin from pulp bleaching wastewater were studied through the structural characterization with 31P-NMR. Lac/GO was able to perform the most extensive oxidation of the chlorinated lignin, as demonstrated by the increase of carboxyl groups and the decrease of aliphatic hydroxyl groups. Noteworthy, significant degradation of condensed lignin substructures occurred during Lac/GO catalyzed oxidation of chlorinated lignin was observed, while the content of phenolic hydroxyl groups of chlorinated lignin substantially increased due to the cleavage of β-O-4 bonds compared to molecular sieve-immobilized laccases. It was also proved that catalytic degradation using Lac/GO as a biocatalyst is the effective method to reduce pollution load of pulp bleaching wastewater. The maximum degradation of chlorinated lignin in pulp bleaching wastewater was achieved with the degradation rate of chlorinated lignin of 88.6% at 5.0 g/L Lac/GO dose, 50 °C, 4 h, pH 5.0. The removal of COD, TOC, and colour was 86.2, 85.8 and 92.2%, respectively.